PENERAPAN MODEL PROBLEM BASED LEARNING DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Nastiti, Annida Putri; Al Husna, Salsabillah Rizki; Sa’diyyah, Salwa; Marini, Arita; Yunus, Mahmud (Cahaya Ilmu Bangsa Institute, 2024)
Social studies in elementary school has a crucial role in forming the character and basic knowledge of students about their social environment. However, the monotonous learning process makes the effectiveness of learning low. This research aims to examine the effectiveness of the application of the Problem Based Learning (PBL) learning model in social studies in elementary schools. The main focus of this research is the application of the PBL model in improving student learning outcomes. This type of research is library research. Data collection is based on online searches. The results of the analysis of 9 journals show that the Problem Based Learning (PBL) model has a positive impact on learning, which can improve student learning outcomes in social studies. Pembelajaran IPS di sekolah dasar memegang peranan krusial dalam membentuk karakter dan pengetahuan dasar siswa tentang lingkungan sosialnya. Namun proses pembelajaran yang monoton membuat rendahnya efektivitas pembelajaran. Penelitian ini bertujuan untuk mengkaji efektivitas penerapan model pembelajaran Problem Based Learning (PBL) pada mata pelajaran IPS di sekolah dasar. Fokus utama penelitian ini adalah penerapan model PBL dalam meningkatkan hasil belajar siswa. Jenis penelitian ini adalah penelitian studi pustaka (Library Research). Pengumpulan data dilakukan melalui penelusuran secara online. Hasil analisis dari 9 jurnal menunjukkan bahwa model Problem Based Learning (PBL) memberi dampak positif terhadap pembelajaran, yaitu dapat meningkatkan hasil belajar siswa pada mata pelajaran IPS.